问题
解答题
|
答案
(1)
×5 7
+1 4
×3 4
,5 7
=(
+1 4
)×3 4
,5 7
=1×
,5 7
=
;5 7
(2)(13+
)×1 9
,9 13
=13×
+9 13
×1 9
,9 13
=9+
,1 13
=9
;1 13
(3)
×12+66 13
,66 13
=(12+1)×
,66 13
=13×
,66 13
=66;
(4)
×4 5
×3 8
,5 9
=
×3 10
,5 9
=
;1 6
(5)
×(8 3
-1 3
×8 21
),8 16
=
×(8 3
-1 3
),8 42
=
×8 3
,1 7
=
;8 21
(6)
×11-9 10
,9 10
=(11-1)×
,9 10
=10×
,9 10
=9;
(7)
×34×7×1 7
,2 17
=(
×7)×(34×1 7
),2 17
=1×4,
=4;
(8)
+1 3
+4 7
+2 3
,1 7
=(
+1 3
)+(2 3
+4 7
),1 7
=1+
,5 7
=1
;5 7
(9)
×48,6 47
=
×47+6 47
×1,6 47
=6+
,6 47
=6
.6 47